A general approach to welfare measurement through national income accounting - Geir B. Asheim; Wolfgang Buchholz (University of Oslo, Department of Economics, 2002)
We develop a framework for analyzing national income accounting using a revealed welfare approach that is sufficiently general to cover, e.g., both the standard discounted utilitarian and maximin criteria as special cases. We show that the basic welfare properties of comprehensive national income accounting, which were previously ascribed only to the discounted utilitarian case, in fact extend to this more general framework. In particular, it holds under a wide range of circumstances that real nnp growth (or equivalently, a positive value of net investments) indicates welfare improvement. We illustrate the applicability of our approach by considering resource allocation mechanisms in the Dasgupta-Heal-Solow model of capital accumulation and resource depletion.
Keywords: C43; O47; Q01; 330; National income accounting; dynamic welfare; Volkswirtschaftliche Gesamtrechnung; Soziale Wohlfahrtsfunktion; Theorie